In vitro comparative quality assessment of different brands of hydrochlorothiazide tablets marketed in Northeast Ethiopia - Wondmkun, Yehualashet Teshome; Desta, Haile Kassahun; Ali, Yimer Seid; Tsige, Abate Wondesen; Ayenew, Kassahun Dires; Endalifer, Bedilu Linger; Dagnew, Samuel Berihun (Frontiers in Analytical Science, 2024)
Background This study aimed to comparatively evaluate the quality and physicochemical bioequivalence of commercially available brands of hydrochlorothiazide (HCT) tablets in community pharmacies in Dessie town, Northeast Ethiopia. Methods Experimental cross-sectional study design was applied using pharmacopeia and non-pharmacopeia methods. The difference (f1) and similarity (f2) factors were calculated to assess the in vitro bioequivalence of generic products with the comparator. Result The study results revealed that all investigated brands contained the required active pharmaceutical ingredients (APIs). The friability test results were concordant with the United States Pharmacopeia (USP) (<1%) for eight brands; however, brand NF3 (1.36%) failed to pass the specification limit. The hardness levels of the brands NF3 (24.20 ± 7.32 N), NF5 (32.19 ± 4.78 N), and NF9 (35.02 ± 3.12 N) were below the specification limit (39.23 N, USP 2019). The weight variation results of all generic products complied with the USP specification requirement. In the quantitative assay results, the minimum and maximum API contents were 97.4 ± 0.02 (NF6) and 105.8 ± 0.02 (NF8), respectively, which are within the limit specified by the USP (90%–110%). Similarly, all samples met the disintegration time limit (i.e., ≤30 min) and drug-releasing tolerance limit (API released more than 60% within 60 min) requirements. The f2 values were >50, and the f1 values were <15 for all sampled brands. Conclusion The majority of the sampled brands of HCT tablets met the quality requirements as per USP official test specifications. From the similarity and difference factor values, all studied brands were shown to be equivalent.